Depth Perception and the History of Three-Dimensional Art: Who Produced the First Stereoscopic Images? - Kevin R. Brooks (i-Perception, 2017)
The history of the expression of three-dimensional structure in art can be traced from the use of occlusion in Palaeolithic cave paintings, through the use of shadow in classical art, to the development of perspective during the Renaissance. However, the history of the use of stereoscopic techniques is controversial. Although the first undisputed stereoscopic images were presented by Wheatstone in 1838, it has been claimed that two sketches by Jacopo Chimenti da Empoli (c. 1600) can be to be fused to yield an impression of stereoscopic depth, while others suggest that Leonardo da Vinci’s Mona Lisa is the world’s first stereogram. Here, we report the first quantitative study of perceived depth in these works, in addition to more recent works by Salvador Dalí. To control for the contribution of monocular depth cues, ratings of the magnitude and coherence of depth were recorded for both stereoscopic and pseudoscopic presentations, with a genuine contribution of stereoscopic cues revealed by a difference between these scores. Although effects were clear for Wheatstone and Dalí’s images, no such effects could be found for works produced earlier. As such, we have no evidence to reject the conventional view that the first producer of stereoscopic imagery was Sir Charles Wheatstone.